Konten Youtube Sebagai Objek Jaminan Fidusia Berbasis Pembiayaan Kekayaan Intelektual - Ahmad Bahyj Gunawan; Pandam Nurwulan (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to find out the youtube content that is used as an object of fiduciary guarantee based on intellectual property financing. The problem in this research is whether YouTube content can be used as a fiduciary guarantee and the criteria for YouTube content that can be used as a fiduciary guarantee. The research method used in this research is normative legal research. The research approach is statute approach, conceptual approach, and case approach. The legal materials used are primary legal materials and secondary legal materials. Based on the results of the research conducted, that youtube accounts can be used as fiduciary guarantees using intellectual property-based financing schemes provided that they meet specific criteria that meet the copyright (copy right) provisions that have been determined by youtube and are in line with Law No.28 of 2014 concerning Copyright. Meanwhile, the criteria for YouTube content that can be used as an object of fiduciary guarantee is YouTube content that meets the criteria for originality. This is the embodiment of ideas or the result of creativity generated from the creator's own mind, so that originality becomes a legal requirement that must be met so that a creation can obtain certainty of legal protection. Originality does not require novelty in a work, but it does require that a work is truly the result of the creator's thoughts/creation.